Project-Based Electronic Module Development As A Supporting Learning Media For Basic Programming Learning - Reny Kartika Ningtyas; Handaru Jati (Journal of Educational Science and Technology (EST), 2018)
This study aims to develop and determine the feasibility of electronic modules or e-modules based on the project based learning (PBL) method in Basic Programming Subjects at SMK Negeri 1 Japara Kuningan, West Java. This study uses research and development methods. The development procedure adopts the Lee and Owens model with four stages, namely: analysis stage, design stage, developing and implementation stage, and evaluation stage. At the evaluation stage several stages are carried out, namely: Alpha test to determine the validity of product feasibility conducted by material experts and design expert. Then proceed with a beta test carried out to one group. The research subjects were students of class X majoring in Multimedia. The instrument used in this research is a validation sheet and questionnaire sheet. The results of the qualitative data will be converted into quantitative data using a scale from 1 to 4, then the rating scale is converted to determine the feasibility of the project based learning e-module PBL. The results show that the appraisal of the feasibility of the product gets a decent feasibility from the design expert and is very feasible from the material expert. Evaluation on beta tests found that 8.6% considered quite feasible, 71.4% said it was feasible, and 20% said it was very feasible.